2020
DOI: 10.1007/s11222-020-09921-1
|View full text |Cite
|
Sign up to set email alerts
|

Detecting anomalies in fibre systems using 3-dimensional image data

Abstract: We consider the problem of detecting anomalies in the directional distribution of fibre materials observed in 3D images. We divide the image into a set of scanning windows and classify them into two clusters: homogeneous material and anomaly. Based on a sample of estimated local fibre directions, for each scanning window we compute several classification attributes, namely the coordinate wise means of local fibre directions, the entropy of the directional distribution, and a combination of them. We also propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The experiment is repeated for a random sample from the P 3 (γ) distribution with γ = 3, and the value of W P 1000,1 (3, γ) computed for different values of γ in the range [1,6]. The results are shown in Figure 11, where we see that the statistic reaches a minimum value at approximately γ = 3.…”
Section: Point Estimationmentioning
confidence: 98%
See 1 more Smart Citation
“…The experiment is repeated for a random sample from the P 3 (γ) distribution with γ = 3, and the value of W P 1000,1 (3, γ) computed for different values of γ in the range [1,6]. The results are shown in Figure 11, where we see that the statistic reaches a minimum value at approximately γ = 3.…”
Section: Point Estimationmentioning
confidence: 98%
“…An entropy-based goodness-of-fit test for generalized Gaussian distributions is presented by [3]. A recent application to image processing can be found in [6].…”
Section: Introductionmentioning
confidence: 99%
“…4b (left). The detailed description of the material can be found in (Wirjadi et al, 2014) and it was the object of studies in (Dresvyanskiy et al, 2019) and (Dresvyanskiy et al, 2020), where the regions of anomaly behaviour of the fibres were found. The data set is provided by Prof. Claudia Redenbach (TU Kaiserslautern) and consists of local direction of fibres estimated by the tools of MAVI software (Fraunhofer ITWM, Department of Image Processing, 2005).…”
Section: Test Statisticmentioning
confidence: 99%
“…Directional distributions characterize randomness in unit vectors (directions). Spherical data sets appear in a wide range of problems arising from Earth sciences (Pischiutta et al, 2013), oceanography (Wyatt et al, 1997;Shabani et al, 2016), biology (Mouritsen & Mouritsen, 2000), physics (Torrance et al, 1966), material science (Dresvyanskiy et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the goal of density approximation, the possibility of modeling latent features by the underlying components make it also a strong tool for soft clustering tasks. Typical applications are to be found in the area of image analysis (Alfò et al 2008;Dresvyanskiy et al 2020;Zoran and Weiss 2012), pattern recognition (Wu et al 2012;Bishop 2006), econometrics (Articus and Burgard 2014;Compiani and Kitamura 2016 and many others).…”
Section: Introductionmentioning
confidence: 99%